E-COMMERCE HYPERREALITY ON PRIVATE WORKERS' CONSUMER BEHAVIOR: A COMPARISON IN SURABAYA CITY (INDONESIA) AND DUBLIN CITY (IRELAND) - Febiyanti Risca Sabila; Muhammad Fakhrur Rozi; Tasya Annisa Syahnindita (Jurnal Analisa Sosiologi, 2025)
This study aims to determine the effect of e-commerce hyperreality on the consumer behavior of private employees in Surabaya City and Dublin City. This study uses a quantitative correlational approach. Correlation research is a study that aims to see the form of relationship between two variables. The sample of this study consisted of 50 respondents, consisting of private employees in Surabaya City and five private worker informants in Dublin City, Ireland. The instrument in this study was a questionnaire consisting of 24 questions covering the identity of the respondents, the intensity of accessing e-commerce, interest in the image displayed by e-commerce, the type of goods purchased, and the amount of funds spent to buy goods on e-commerce. Data were analyzed using descriptive statistics to identify the characteristics of respondents, as well as Pearson correlation and Linearity Test to evaluate the relationship and influence of e-commerce hyperreality on consumer behavior. The results showed that private workers in Surabaya City used e-commerce more often than private workers in Dublin City. Private workers in Surabaya City have the reason that e-commerce prices are cheaper than those in offline stores. This study contributes to national and international literature by focusing on the influence of e-commerce on consumer behavior in the context of urban society. Practically, the data findings in this study can be used by the entire community to be wiser in using e-commerce, in the sense of buying goods based on needs, not because discounts and good-looking images tempt them.